IMPROVEMENT OF ANALYTICAL OPERATIONS USED IN THE AUDIT OF PRODUCTION PROCESSES IN ENTITY - Kahharova Ezoza Kahramon qizi (Research Parks Publishers, 2023)
The article examines the analytical operations used in the audit of production processes in economic entities. As a result of the research, proposals were developed on the implementation of analytical procedures used in the audit of production processes based on international standards.